Individuals with SATB2-associated syndrome have impaired vitamin and energy metabolism pathways - Roberto Collu; Yuri A. Zarate; Weiming Xia; Jennifer L. Fish (Metabolic Brain Disease, 2024)

Kinematics of terrestrial locomotion in harbor seals and gray seals: Importance of spinal flexion by amphibious phocids - Jennifer N. Garrett; Frank E. Fish (Marine Mammal Science, 2015)
Pinnipeds are amphibious mammals with flippers, which function for both aquatic and terrestrial locomotion. Evolution of the flippers has placed constraints on the terrestrial locomotion of phocid seals. The detailed kinematics of terrestrial locomotion of gray ( Halichoerus grypus ) and harbor ( Phoca vitulina ) seals was studied in captivity and in the wild using video analysis. The seals exhibited dorsoventral undulations with the chest and pelvis serving as the main contact points. An anteriorly directed wave produced by spinal flexion aided in lifting the chest off the ground as the fore flippers were retracted to pull the body forward. The highest length‐specific speeds recorded were 1.02 BL /s for a gray seal in captivity and 1.38 BL /s for a harbor seal in the wild. The frequency and amplitude of spinal movement increased directly with speed, but the duty factor remained constant. Substrate did not influence the kinematics except for differences due to moving up or down slopes. The highly aquatic nature of phocids seals has restricted them to locomote on land primarily using spinal flexion, which can limit performance in speed and duration.

A geomorphological mapping approach for the assessment of seabed geohazards and risk - Gayle Hough; Jennifer Green; Paul Fish; Andy Mills; Roger Moore (Marine Geophysical Research, 2011)

Selection, Morphological Integration, and Strepsirrhine Locomotor Adaptations - Brian Villmoare; Jennifer Fish; William Jungers (Evolutionary Biology, 2011)

Predicting the Impact of Sea‐Level Rise on Caribbean Sea Turtle Nesting Habitat - MARIANNE R. FISH; ISABELLE M. CÔTÉ; JENNIFER A. GILL; ANDREW P. JONES; SASKIA RENSHOFF; ANDREW R. WATKINSON (Conservation Biology, 2005)
The projected rise in sea level is likely to increase the vulnerability of coastal zones in the Caribbean, which are already under pressure from a combination of anthropogenic activities and natural processes. One of the major effects will be a loss of beach habitat, which provides nesting sites for endangered sea turtles. To assess the potential impacts of sea‐level rise on sea turtle nesting habitat, we used beach profile measurements of turtle nesting beaches on Bonaire, Netherlands Antilles, to develop elevation models of individual beaches in a geographic information system. These models were then used to quantify areas of beach vulnerable to three different scenarios of a rise in sea level. Physical characteristics of the beaches were also recorded and related to beach vulnerability, flooding, and nesting frequency. Beaches varied in physical characteristics and therefore in their vulnerability to flooding. Up to 32% of the total current beach area could be lost with a 0.5‐m rise in sea level, with lower, narrower beaches being the most vulnerable. Vulnerability varied with land use adjacent to the beach. These predictions about loss of nesting habitat have important implications for turtle populations in the region.

HIGH PERFORMANCE TURNING CAPABILITIES DURING FORAGING BY BOTTLENOSE DOLPHINS ( TURSIOPS TRUNCATUS ) - Jennifer L. Maresh; Frank E. Fish; Douglas P. Nowacek; Stephanie M. Nowacek; Randall S. Wells (Marine Mammal Science, 2004)
A bstract Large predators should have difficulty catching small prey because small animals demonstrate greater maneuverability and agility compared to large animals. The ability of a predator to capture small prey indicates locomotor strategies to compensate for inequities in maneuverability. Bottlenose dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida feed on fish at least one order of magnitude smaller than themselves. To examine the locomotor strategies involved in prey capture, the foraging movements of these dolphins were videotaped from overhead using a remotely‐controlled camera suspended from a helium‐filled aerostat, which was tethered to an observation vessel. Dolphins were observed to rapidly maneuver during chases of fish in open water or around patches of rooted vegetation. Video analysis of the chase sequences indicated that the dolphins could move the rostrum through small radius turns with a mean value of 0.20 body lengths and with a minimum value of 0.08 body lengths. Mean rate of turn was 561.6°/sec with a maximum rate measured at 1,372.0°/sec. High turning rates with small turning radii were primarily the result of maneuvers in which the dolphin rolled 90° and rapidly flexed its body ventrally. The ability of dolphins to change body orientation in multiple rotational axes provides a mechanism to reduce turning radius and increase turning rate to catch small, elusive prey.